The effect of various nutrient media on the captured diversity of culturable seed endophytes in European beech (Fagus sylvatica L.) - Stolarek, Kinga (2022)
The associations of fungal endophytes with trees are poorly understood, especially within tree seeds. Recent molecular studies show that tree seeds harbour highly diverse fungal communities, including potential plant pathogens that could be introduced to new areas when seeds are exchanged. However, only a small fraction of these fungi can be detected when traditional culturing is used. Traditional culturing is widely used for assessing fungal diversity in plant tissues because it allows the detection of viable fungi and provides pure isolates for future experiments. However, various nutrient media have been used for fungal culturing and it is unknown if the choice of nutrient media affects the captured diversity. This study assesses the overall diversity of endophytes in seeds of European beech (Fagus sylvatica L.) and tests the effect of media and seed origins on endophyte diversity by growing fungi from seeds from six locations on three commonly used types of media that differ in carbon sources (Malt Extract Agar, Potato Dextrose Agar and Water Agar). The results show that almost all tested seeds of European beech yielded fungi, and reveal high diversity of fungal endophytes, including plant pathogens. Captured diversity and community composition stayed unchanged irrespective of the medium type, but it differed across locations of seed origin. The results show that similar communities are obtained using three most commonly used media which indicates that most of the fungi are able to utilise simple and complex carbohydrates and allows comparison of diversity assessed by those media. The results also indicate that dangerous fungal pathogens could be moved within the seeds exchanged for tree reforestation purposes which calls for the use of local seeds for reforestation.